2021
DOI: 10.1002/smi.3052
|View full text |Cite
|
Sign up to set email alerts
|

Did you get that thing I sent you? Mediating effects of strain and work‐family conflict on the telepressure and burnout relationship

Abstract: Employees who feel the urge and preoccupation to respond to workplace asynchronous communication quickly may be suffering from workplace telepressure (WPT). Although information and communication technologies have many organizational benefits, it is imperative to understand the cost of blurring work and family roles. Using the Job Demands‐Resources model, the relationship between WPT and key outcomes, such as strain, work‐family conflict, family‐work conflict (FWC), and burnout was examined. In Study 1, a samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 79 publications
3
16
1
1
Order By: Relevance
“…Similar associations between job demands and employees' levels of job satisfaction, ill-health and turnover intentions (Huynh et al, 2014;Koon and Pun, 2018) have been found to be mediated by their levels of emotional exhaustion. Thus, and in line with previous studies demonstrating similar indirect effects of workplace connectivity on the work-family interface and well-being (Barber et al, 2019;Page et al, 2021), we hypothesize that:…”
Section: The Undesirable Effects Of Emotional Exhaustionsupporting
confidence: 89%
See 3 more Smart Citations
“…Similar associations between job demands and employees' levels of job satisfaction, ill-health and turnover intentions (Huynh et al, 2014;Koon and Pun, 2018) have been found to be mediated by their levels of emotional exhaustion. Thus, and in line with previous studies demonstrating similar indirect effects of workplace connectivity on the work-family interface and well-being (Barber et al, 2019;Page et al, 2021), we hypothesize that:…”
Section: The Undesirable Effects Of Emotional Exhaustionsupporting
confidence: 89%
“…family satisfaction, life satisfaction and sleep quality) based on theoretical grounds (Bakker et al. , 2010; Page et al. , 2021), our cross-sectional design makes it impossible to confirm the directionality of these associations.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Numerous studies have demonstrated the detrimental effects of job demands on workers' attitudes (e.g., job satisfaction), behaviors (e.g., work performance), and health (e.g., psychological well-being; Park et al, 2020;Voydanoff, 2015). In addition, many researchers working with the JD-R model have emphasized the need to try and identify the mediating variables explaining the effects of job demands, and the dimensions (e.g., job resources) that moderate these effects (e.g., Derks et al, 2015;Page et al, 2021). In this regard, research has shown that the negative effects of job demands may be explained by a variety of individual (e.g., psychological need satisfaction) and collective (e.g., team effectiveness) variables (Gillet et al, 2015;Leicht-Deobald et al, 2022).…”
Section: The Detrimental Effects Of Job Demandsmentioning
confidence: 99%